IMPLEMENTASI PEMBELAJARAN KOOPERATIF TEKNIK LINGKARAN KECIL LINGKARAN BESAR UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS V SD NEGERI 018 PAGARUYUNG KECAMATAN TAPUNG KABUPATEN KAMPAR - Helpen Holis (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This study aims to determine whether the application of cooperative learning model small circle circle techniquecan improve learning outcomes civics student grade V SD Negeri 018 Pagaruyung Kecamatan TapungKabupaten Kampar. The study was conducted in two cycles, each cycle consisting of three meetings startingfrom April 2016 to May 2016. The study instrument consists of learning instrument instruments and datacollection instruments in the form of student activity observation sheets, and student learning outcomes. Thedata in this study are data about: Data on the application of cooperative learning model small circle circletechnique, ie data about student activity and teacher activity in learning obtained through observation sheet anddata about student learning outcomes in learning obtained through the test of learning outcomes . This researchis said to be successful if the learning outcomes that achieve learning mastery in learning Civics with theapplication of cooperative learning model techniques small circle small circle reaches 75%. Based on the resultsof presentation and discussion is known that the cycle I classical completeness of 45,5%, then the cycle IIclassical completeness reached 81,8%. Thus there was an increase of 36,3%.